Pengelolaan Aset Tanah Milik Pemerintah Kota Semarang - Krisindarto, Agung (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2012)
In the regional autonomy era, Semarang City’s Administration has put efforts towards independent development financing in its region, one of them through the management cycle of land as a regional asset. The Semarang City Administration is putting it in practice in accordance with the national regulation. However, several problems have started to occur, such as: unclear actual land ownership status and its legal standings, along with low revenue coming from this sector to the regional income. The study uses positivistic-rationalistic approach through descriptive analysis, IPA analysis (Importance-Performance Analysis), and regional financial independence ratio analysis. The study found that Semarang City Administration’s land asset management has several shortcomings, including: management weaknesses, and the absence of asset management optimizing strategy. The study recommends the following, in order to improve the regional finance independence, Semarang City Administration: (1) review of the existing land asset management cycle, and (2) establishment of asset optimizing strategic plan.